2014
DOI: 10.1371/journal.pntd.0002670
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the NSm Virulence Gene of Rift Valley Fever Virus Inhibits Virus Replication in and Dissemination from the Midgut of Aedes aegypti Mosquitoes

Abstract: BackgroundPreviously, we investigated the role of the Rift Valley fever virus (RVFV) virulence genes NSs and NSm in mosquitoes and demonstrated that deletion of NSm significantly reduced the infection, dissemination, and transmission rates of RVFV in Aedes aegypti mosquitoes. The specific aim of this study was to further characterize midgut infection and escape barriers of RVFV in Ae. aegypti infected with reverse genetics-generated wild type RVFV (rRVF-wt) or RVFV lacking the NSm virulence gene (rRVF-ΔNSm) by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
59
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 31 publications
7
59
1
1
Order By: Relevance
“…Work on BUNV NSm demonstrated that the protein can localize to the Golgi efficiently on its own (46) and may play a role in viral assembly (47). In Rift Valley fever virus (RVFV), the NSm protein is important for infection in mosquitoes by allowing the virus to cross the midgut barrier (48,49). Similarly, in tospoviruses, the NSm protein has been shown to be important for virus cell-to-cell spread (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…Work on BUNV NSm demonstrated that the protein can localize to the Golgi efficiently on its own (46) and may play a role in viral assembly (47). In Rift Valley fever virus (RVFV), the NSm protein is important for infection in mosquitoes by allowing the virus to cross the midgut barrier (48,49). Similarly, in tospoviruses, the NSm protein has been shown to be important for virus cell-to-cell spread (50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…A major virulence factor, NSs, is a nonstructural protein dispensable for viral replication (46,47) and plays a major role in counteracting the innate immunity of the host, e.g., by (i) shutting off of host cell transcription by interacting with TFIIH p44 (48) and by promoting the degradation of TFIIH p62 (49,50), (ii) specific inhibition of the beta interferon (IFN-␤) promoter (51,52), and (iii) posttranslational degradation of double-stranded RNA-dependent protein kinase (PKR) (53,54). Another nonstructural protein, NSm, has a role in delaying apoptosis in mammalian cells (55,56), while it is involved in the efficient transmission of virus in mosquitoes (57,58). The 78-kDa protein is a structural protein for virions derived from mosquito C6/36 cells but not for those derived from VeroE6 cells (3,59).…”
mentioning
confidence: 99%
“…The NSs protein, the major virulence factor, has been shown to inhibit host transcriptional immune response (Bouloy et al 2001) through generalized transcription downregulation, including repression of interferon-b (IFN-b) , Le May et al 2004, Le May et al 2008) and degradation of protein kinase R , Ikegami et al 2009). The NSm protein functions to suppress virus-induced apoptosis (Won et al 2007), and there is evidence that it plays a functional role in the vector competence of mosquitos for RVFV at the level of the midgut barrier (Kading et al 2014). The glycoproteins Gn and Gc are surface proteins that play a role in virus attachment to initiate infection and have been shown to carry epitopes that elicit the production of neutralizing antibodies, a correlate of protective immunity (Besselaar et al 1991, Besselaar and Blackburn 1992, Besselaar and Blackburn 1994.…”
mentioning
confidence: 99%